Marquis de Sade and continental philosophy - Lauwaert, Lode, 1981- (Edinburh University Press, 2019)
Reads six interpretations of the Marquis de Sade in French post-war philosophy: Klossowski, Blanchot, Bataille, Lacan, Barthes, and Deleuze to show how he sits at a crossroads of surprisingly disparate branches of western culture, from Tom and Jerry to Kant's moral philosophy.